Studi Fenomenologi: Perilaku Keuangan Para Penggemar Idol Group JKT48 - Ilham Ramadhan Ersyafdi; Fitriah Ulfah (LPPM POLITEKNIK LP3I BANDUNG, 2026)
This study examines the financial behavior of JKT48 fans using a qualitative phenomenological approach, focusing on how fans experience and interpret financial decisions related to idol fandom activities. The research aims to understand the meanings attached to spending behavior beyond rational economic considerations. Data was collected through in-depth interviews with active JKT48 fans and analyzed using interpretative phenomenological analysis to capture participants lived experiences. The findings reveal that fans’ financial behavior is primarily shaped by emotional attachment and parasocial relationships with idols. Expenditures on theater performances, handshake events, concerts, and official merchandise are perceived as expressions of loyalty and emotional investment rather than ordinary consumption. JKT48’s “idols you can meet” business model plays a central role in monetizing emotional closeness and perceived intimacy, which encourages repeated purchasing and sustained fan loyalty. Furthermore, fans apply an event-driven budgeting strategy, in which financial planning is organized around the fandom event calendar rather than routine monthly budgeting. Funds allocated for fandom activities are given priority due to their emotional value, leading fans to postpone trade-offs with other personal expenses. This behavior reflects a negotiation between emotional fulfillment and financial rationality. Overall, the study demonstrates that the financial behavior of JKT48 fans is embedded in emotional, social, and experiential contexts. These findings contribute to behavioral finance and fandom studies by providing insight into fandom-related financial behavior and offering implications for ethical fandom management and financial literacy.